After an initial balance favoring collagen formation and mineralization, bone turnover markers return to pre-treatment levels during long-term TNF-α inhibition in patients with ankylosing spondylitis. - Mark Siderius; Anneke Spoorenberg; Frans G M Kroese; Eveline van der Veer; Suzanne Arends (PLoS ONE, 2023)
Background Bone turnover balance favors bone formation, especially mineralization, during the first 3 years of treatment with TNF-α inhibitors (TNFi). Our aim was to evaluate the course of serum bone turnover markers (BTM) and to investigate if facilitation of mineralization reflected by BTM BALP continues to increase during 6 years of TNFi treatment in patients with ankylosing spondylitis (AS) in daily clinical practice. Methods Included were outpatients from the University Medical Center Groningen (UMCG) participating in the Groningen Leeuwarden Axial SpA (GLAS) cohort who were treated with TNFi for at least 6 years. Serum markers of collagen resorption, bone regulation, collagen formation and facilitator of bone mineralization (sCTX, OC, PINP and BALP, respectively) were measured at baseline, 3 and 6 months, 1, 2, 4 and 6 years. Z-scores were calculated to correct for age and gender. Results 53 AS patients were eligible for analyses (66% male, mean age 39±11 years). Disease activity showed rapid and sustained improvement after start of TNFi. Evaluating BTM, sCTX did not significantly change during 6 years of treatment. OC was only significantly increased at 3 months compared to baseline, with median change in Z-score of +0.5. PINP significantly increased at 3 and 6 months and 2 years of treatment, with maximum median change in Z-score of +0.3. Interestingly, BALP was significantly increased at all time points up to and including 2 years of TNFi treatment, with maximum change in median Z-score of +1.2, and decreased thereafter. Conclusion In AS patients receiving long-term TNFi, bone turnover balance favored collagen formation and facilitation of mineralization during the first 2 years of treatment. Thereafter, at 4 and 6 years of follow-up, BTM Z-scores returned to pre-treatment levels.